2006
DOI: 10.1021/ed083p1322
|View full text |Cite
|
Sign up to set email alerts
|

Using Physical Models of Biomolecular Structures To Teach Concepts of Biochemical Structure and Structure Depiction in the Introductory Chemistry Laboratory

Abstract: Basic concepts of biomolecular structure were introduced to students in the laboratory portion of a large-enrollment first-year chemistry class. Custom-made physical models of α-helices and β-sheets, the zinc finger moiety, β-globin, and green fluorescent protein were used. α-Helix and DNA construction kits were also employed. Students investigated primary, secondary, and tertiary structure of proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
(1 reference statement)
1
18
0
Order By: Relevance
“…In 1998, Leon et al published a biochemistry laboratory project in which students used internet websites and freeware to model protein structure [31]. 1 Leon et al describe a project in which students select a protein whose structure has already been solved and deposited in the Protein Data Bank (PDB). They then carry out a series of four operations on the internet: (a) use search programs to find a "novel homolog," i.e., a homologous protein whose structure has NOT yet been solved; (b) submit the amino acid sequence of the novel homolog to secondary structure prediction programs and compare secondary structures of the original protein and its novel homolog; (c) submit the amino acid sequence of the novel homolog to Swiss Model to obtain a predicted three-dimensional structure; and finally (d) compare the 3D structure of original protein to that of its novel homolog.…”
Section: Period 3 Part Ib: Myoglobin Function: Ligand Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1998, Leon et al published a biochemistry laboratory project in which students used internet websites and freeware to model protein structure [31]. 1 Leon et al describe a project in which students select a protein whose structure has already been solved and deposited in the Protein Data Bank (PDB). They then carry out a series of four operations on the internet: (a) use search programs to find a "novel homolog," i.e., a homologous protein whose structure has NOT yet been solved; (b) submit the amino acid sequence of the novel homolog to secondary structure prediction programs and compare secondary structures of the original protein and its novel homolog; (c) submit the amino acid sequence of the novel homolog to Swiss Model to obtain a predicted three-dimensional structure; and finally (d) compare the 3D structure of original protein to that of its novel homolog.…”
Section: Period 3 Part Ib: Myoglobin Function: Ligand Bindingmentioning
confidence: 99%
“…Besides these and other similarities, six key differences between the two forms of Mb are marked above. 1 In order to increase the diversity of protein structures examined, we have half of the students start with myoglobin, a predominantly alpha-helical protein, and the other half start with the predominantly beta-sheet protein, lysozyme.…”
Section: Periods 4 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of successive bases is easily recognized by numbering (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and it can be followed from both sides because of the transparency of the sheets the base pairs are printed on. One letter nucleotide codes (A, T, C, G) are also written in color.…”
Section: Model Building and Ways To Show Biochemical Detailsmentioning
confidence: 99%
“…We have found that many students fail to grasp three-dimensional details when DNA and protein structures are introduced in these ways. Several physical models of DNA and protein made of paper, wooden, metallic or plastic materials have been developed for teaching purposes [1][2][3][4][5][6][7][8][9][10]. These have features useful for illustrating certain important structural aspects of these molecules.…”
mentioning
confidence: 99%